2001
DOI: 10.1590/s1516-31802001000600006
|View full text |Cite
|
Sign up to set email alerts
|

p53 gene analysis in childhood B non - Hodgkin's lymphoma

Abstract: These preliminary results suggest that p53 mutations are quite frequent in children with Burkitt's lymphoma and may play a role in lymphoma genesis or disease progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 23 publications
0
6
1
Order By: Relevance
“…33 The presence of the p53 gene has been correlated with a more aggressive behavior, clinical progression, histologic transformation, and resistance to chemotherapy. In our population, the incidence of p53 overexpression was high at 81% (39/48) compared with other pediatric series: Klumb et al reported 36% in Brazilian children with NHL, 28,29 and Preciado et al reported 68% in Argentinean children with Hodgkin lymphoma. 32 Moreover, our NHL patients showed higher p53 overexpression than adults with NHL from developed countries, where p53 positivity ranged from 30% to 60%.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…33 The presence of the p53 gene has been correlated with a more aggressive behavior, clinical progression, histologic transformation, and resistance to chemotherapy. In our population, the incidence of p53 overexpression was high at 81% (39/48) compared with other pediatric series: Klumb et al reported 36% in Brazilian children with NHL, 28,29 and Preciado et al reported 68% in Argentinean children with Hodgkin lymphoma. 32 Moreover, our NHL patients showed higher p53 overexpression than adults with NHL from developed countries, where p53 positivity ranged from 30% to 60%.…”
Section: Discussioncontrasting
confidence: 52%
“…9 Overexpression of p53, p21 waf1 , and bcl-2 has been largely studied in adults with NHL 10-27 and some pediatric populations. 28,29 Correlation with clinical features and survival has been evaluated. Our aim was to analyze overexpression of these cellular oncogenes and to correlate these findings with patient outcomes in an Argentinean population of children wilh NHL.…”
mentioning
confidence: 99%
“…This number lies at the lower border of the range of published series of BL biopsies (20-40%), which is lower than in BL cell lines (60-70%). [23][24][25][26][27][31][32][33][34] As in other studies, p53 mutations in our patients with BL cluster in exon 7 (Table 2, codon 245 and 246), which codes for the DNAbinding domain of p53. 24,34 The mutation of codon 92 has only been described in three tumors so far.…”
Section: Resultsmentioning
confidence: 82%
“…P53 mutations have been found in 20-40% of BL/B-ALL. [23][24][25][26][27] The INK4A/ARF locus was inactivated by deletion in one of 29 BL samples in a series of high-grade non-Hodgkin's lymphomas. 22,[28][29][30] An examination of MDM-2 overexpression has not been reported in tumor samples from BL.…”
Section: Introductionmentioning
confidence: 99%
“…Single‐strand conformation polymorphism (SSCP) analysis is a widely used method in the screening of mutations in these exons. This method is based on the nature of single‐strand DNA to coil into a 3‐D conformation in a non‐denaturing environment, where even one nucleotide change can result in a different conformation, thereby producing variations in electrophoretic mobility 23 . The sensitivity of polymerase chain reaction single‐strand conformation polymorphism (PCR‐SSCP) in detecting variations decreases with an increase in the length of PCR products, and is more than 95% sensitive for PCR products measuring 100–300 bp long, but only approximately 67% sensitive for product sizes measuring 300–500 bp 24 …”
mentioning
confidence: 99%